KEPEMIMPINAN KEPALA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI TENGAH DALAM MENINGKATKAN KINERJA PEGAWAI - Tanjubulu, Mohammad Nasrun; Tjaiya, Abu; Hartawan, Hartawan (Katalogis, 2020)
The theoretical basis used is Stephen Robbins (1996: 20) to see the Effect of Employee Performance at the Department of Manpower and Transmigration in Central Sulawesi Province using four indicators, namely effective thinking in making decisions, communicating thinking results, increasing participation in problem solving, exploring and increasing creativity . This type of research is descriptive which seeks to interpret and interpret data that is pleasing to the facts, using purposive methods, data collection and discussion with a qualitative analysis approach to collecting data and materials through observation and interviews with a total of 5 (five) informants. Based on the results of the interview, it was found that leadership in the influence of employee performance at the Central Sulawesi Provincial Office of Manpower and Transmigration was based on indicators of effective thinking in deciding decisions, communicating thinking results, maximizing participation in problem solving, and exploring and increasing creativity. due to lack of motivation carried out by the Head of the Manpower and Transmigration Office to employees.